Identification of The Addition of Bran and Shallot Extract to the Quantity of Merang Mushroom Production - Hulyadi Hulyadi; Muhali Muhali; Masiah Masiah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
This study aims to identify the addition of bran and onion extract to the quantity of merang mushroom production. This research was carried out at the mushroom house merang Dusun Repok Tunjang Taman Indah Village, Pringgarata District, Lombok center NTB. This research is a descriptive experiment. The study was conducted with treatment and control design. The treatment medium was given fine bran and onion extract while the control added coarse bran rice milling waste. The data obtained are described in the form of graphs and photos. The researchers' findings show that the quality of merang mushroom production in media needs to be 36.03% higher when compared to control media. This is supported by the growth of mycelium, a faster fine head in the treatment medium. The application of bran and onion extract to the growing medium of merang mushrooms has a positive impact on the productivity and quality of merang mushrooms.